Hubungan Motivasi Kerja dan Disiplin Kerja Perawat Ruang Rawat Inap di RSUD Dr.Soekardjo Kota Tasikmalaya - Dzikra Nurfadila Putri; Susan Fitriyana Nugraha; Saleh Trisnadi (Bandung Conference Series: Medical Science, 2023)
Abstract.The low discipline of nurses impacts the low quality of service in a hospital. A factor that can affect the work discipline of nurses is work motivation. Work motivation encourages one to want to work and achieve optimal results. This study aimed to determine the relationship between work motivation and the work discipline of inpatient nurses at RSUD Dr. Soekardjo City of Tasikmalaya. This study used an analytic method with a cross-sectional study design and statistical tests using the Pearson's-chi square test. The sample in this study was inpatient nurses at RSUD Dr. Soekardjo City of Tasikmalaya, totaling 154 people who were obtained through the selection technique of stratified random sampling and met the inclusion and exclusion criteria. The inclusion criteria consisted of nurses working in the Inpatient Room of RSUD Dr. Soekardjo Tasikmalaya City, willing to fill out the questionnaire, and having worked for more than one year in the inpatient room of Dr. Soekardjo and worked in shifts. The exclusion criteria included nurses currently in education, internships, or on leave. This research was carried out in August 2022 by filling in a validated work motivation and discipline questionnaire. The results of the work motivation study were divided into low and medium-high categories with percentages (of 37.7%) and (62.3%). The results of work discipline research are divided into low and medium-high categories with percentages (of 51.3%) and (48.7%). The results of the bivariate analysis found a significant relationship between work motivation and the work discipline of inpatient nurses at RSUD Dr. Soekardjo Kota Tasikmalaya (p = 0.001). Work motivation and work discipline are related to being a driving force to carry out the five indicators of work discipline properly. Abstrak. Rendahnya kedisiplinan perawat berdampak kepada rendahnya kualitas pelayanan di suatu RS. Faktor yang dapat memengaruhi kedisiplinan kerja perawat adalah motivasi kerja, Motivasi kerja memberikan dorongan semangat supaya mau bekerja dan mencapai hasil optimal. Tujuan penelitian ini adalah mengetahui hubungan motivasi kerja dengan disiplin kerja perawat ruang rawat inap di RSUD Dr. Soekardjo Kota Tasikmalaya. Penelitian ini menggunakan metode analitik dengan desain studi cross sectional dan uji statistik menggunakan uji pearson’s-chi square. Sampel pada penelitian ini merupakan perawat ruang rawat inap RSUD Dr. Soekardjo Kota Tasikmalaya berjumlah 154 orang yang didapat melalui teknik pemilihan stratified random sampling dan sudah memenuhi kriteria inklusi serta eksklusi. Kriteria inklusi terdiri dari Perawat yang bekerja di Ruang Rawat Inap RSUD Dr. Soekardjo Kota Tasikmalaya, bersedia mengisi kuesioner, bekerja lebih dari 1 tahun di ruang rawat inap RSUD dr. Soekardjo, dan bekerja di dalam shift. Untuk kriteria eksklusi terdiri dari perawat yang sedang dalam masa pendidikan, magang, ataupun cuti. Penelitian ini dilaksanakan pada Agustus 2022 dengan cara pengisian kuesioner motivasi kerja dan disiplin kerja yang sudah divalidasi. Hasil penelitian motivasi kerja terbagi menjadi kategori rendah dan sedang-tinggi dengan persentase (37,7%) dan (62,3%). Hasil penelitian disiplin kerja terbagi menjadi kategori rendah dan sedang-tinggi dengan persentase (51,3%) dan (48,7%). Hasil analisis bivariat didapatkan adanya hubungan motivasi kerja dengan disiplin kerja perawat ruang rawat inap di RSUD Dr. Soekardjo Kota Tasikmalaya yang signifikan (nilai p=0,001). Motivasi kerja dan disiplin kerja berhubungan dengan menjadi pendorong untuk melaksanakan kelima indikator disiplin kerja dengan baik.